Prognostic role of coronary flow velocity reserve in hypertrophic cardiomyopathy. (25th November 2020) - Tesic, M; Ciampi, Q; Djordjevic-Dikic, A; Beleslin, B; Cortigiani, L; Palinkas, A; Palinkas, E; Nemes, A; Rigo, F; Borguezan-Daros, C; Varga, A; Agoston, G; et al.
Abstract: Background: A reduction in coronary flow velocity reserve (CFVR) related to coronary microvascular dysfunction is a major mechanism for ischemia in hypertrophic cardiomyopathy (HCM). Hypothesis: To assess the functional correlates and prognostic value of CFVR during stress echocardiography (SE) in HCM. Methods: We enrolled 201 HCM patients (age 51±14 years, 105 male, 52%; maximal wall thickness: 18±3 mm) studied with CFVR during exercise (n=33, 16.4%), dipyridamole (n=89, 44.3%) or adenosine (n=79, 39.3%) SE in 6 certified centers. CFVR was assessed using pulsed wave Doppler sampling in left anterior descending coronary artery. All patients completed the clinical follow-up. Results: During SE mean value of CFVR was 2.11±0.46. No patients showed regional wall motion abnormalities during stress. LV outflow tract obstruction (LVOTO) was present in 34 (16.9%) patients at rest and in 47 (23.4%) at peak stress. CFVR was inversely related to age (r=−0.229, p=0.001) and maximal wall thickness (r=−0.197, p=0.031). During a median follow-up of 26 months (IQ range: 12–48 months), 75 events in 63 patients occurred: 10 deaths, 33 new hospital admission for acute heart failure, 8 sustained ventricular tachycardias and 24 atrial fibrillations. Patients in the lowest tertile (≤1.88) showed the worse prognosis with higher incidence of follow-up events compared to median tertile (1.89–2.29) and highest tertile (≥2.30) (see figure). At multivariable analysis, NYHA functional class (HR: 2.234, 95% CI: 1.398–3.517, p=0.001), presence of LVOTO at rest (HR: 2.958, 95% CI: 1.074–3.570, p=0.028) and lowest tertile of CFVR (HR: 2.144, 95% CI: 1.126–4.081, p=0.011) were the independent predictors of follow-up events. Conclusions: In HCM patients, reduction in CFVR is associated to a clearly worse outcome. The spectrum of prognostic stratification is expanded if the response is titrated according to a continuous scale. Funding Acknowledgement: Type of funding source: None